Exploring the Psychological Implications of Aliens in Religion (Global Journal of Human-Social Science, 2024)
The research explores how beliefs in aliens impact human psychology and spirituality examining connections among aliens religion and psychology Through historical analysis and studying religious responses it uncovers how alien beliefs shape perspectives on the divine trigger existential questions and influence spiritual experiences By analyzing alien encounters cosmic quests and scientificreligious interactions it highlights the interplay of psychology beliefs and cosmic connections This study provides insights into evolving spirituality and human consciousness in the era of cosmic exploration deepening understanding of extraterrestrial beliefs on the human psyche and the changing dynamics of spirituality with scientific advancements
Keywords: aliens; religion; psychology of religion; nasa; extraterrestrial life